2015
DOI: 10.3171/2014.10.spine14185
|View full text |Cite
|
Sign up to set email alerts
|

Management of spinal cord injury–related scoliosis using pedicle screw–only constructs

Abstract: OBJECT Almost all pediatric patients who incur a spinal cord injury (SCI) will develop scoliosis, and younger patients are at highest risk for curve progression requiring surgical intervention. Although the use of pedicle screws is increasing in popularity, their impact on SCI-related scoliosis has not been described. The authors retrospectively reviewed the radiographic outcomes of pedicle screw–only constructs in all patients who had undergone SCI-related scoliosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Mayfield et al (10) observed that patients managed for a lumbar hyperlordosis deformity were associated with a secondary hip flexion contracture, and we believe further consideration must be made for these contractures potentially being the primary pathology. Hwang et al (14) reported an uncorrected LL despite spinal surgery, and in our opinion, this may possibly be due to untreated ITB contracturerelated problems. Currently, the literature is too sparse to draw any significant conclusions regarding the relationship between SCI-related hip and spine deformities.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Mayfield et al (10) observed that patients managed for a lumbar hyperlordosis deformity were associated with a secondary hip flexion contracture, and we believe further consideration must be made for these contractures potentially being the primary pathology. Hwang et al (14) reported an uncorrected LL despite spinal surgery, and in our opinion, this may possibly be due to untreated ITB contracturerelated problems. Currently, the literature is too sparse to draw any significant conclusions regarding the relationship between SCI-related hip and spine deformities.…”
Section: Discussionmentioning
confidence: 57%
“…To date, there have been no reports that exclusively manage the paraplegic SCI-associated hip deformity and exaggerated LL. Few have reported operative results of spinal deformities in SCI and poliomyelitis, of which most focus on scoliosis ( 14 ). Furthermore, despite the relationship between the hip and spine being briefly mentioned in the literature, the secondary effects of treating the spine by hip deformity correction have not been investigated.…”
Section: Introductionmentioning
confidence: 99%